2022
DOI: 10.1002/essoar.10512051.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meteorology, not emissions, helps explain an upward trend in atmospheric methane across the US

Abstract: US natural gas production increased by ˜43% between 2005 and 2015, but there is disagreement in the scientific literature on whether this growth led to increased methane emissions. In this study, we evaluate the possible contributions of emissions versus meteorology to an upward trend in US atmospheric methane observations during 2007-2015. We find that interannual variability (IAV) in meteorology yields an apparent upward trend in atmospheric methane across much of the US. We further find that IAV in atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Feng et al. (2022) find that interannual variability in meteorology (especially wind speeds) plays a significant role in trends in CH 4 in the US. Reddy and Pfister (2016) demonstrated that maximum surface ozone concentrations in and near the DDJB are highly correlated with 500 hPa heights.…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al. (2022) find that interannual variability in meteorology (especially wind speeds) plays a significant role in trends in CH 4 in the US. Reddy and Pfister (2016) demonstrated that maximum surface ozone concentrations in and near the DDJB are highly correlated with 500 hPa heights.…”
Section: Resultsmentioning
confidence: 99%
“…China, the largest anthropogenic methane source [Janssens-Maenhout et al, 2019], shows weaker increases. However, such year-to-year comparisons in methane concentrations may have sampling bias and not necessarily relate to changes in emissions because atmospheric transport also drives interannual variability [Bruhwiler et al, 2017;Feng et al, 2021]. The inversion allows us to correct for the effect of transport and isolate the contributions from changes in sources and sinks.…”
Section: Resultsmentioning
confidence: 99%